KEMAMPUAN CALON GURU FISIKADALAM MENGEMBANGKAN MODUL AJAR BERBASIS CULTURALLY RESPONSIVE TEACHING - Hasyim, Mutahharah; Herman, Nurul Muthmainnah; Riskawati, Riskawati; Taqwin, Muhammad (Charm Sains: Jurnal Pendidikan Fisika, 2024)
This study employs a Research and Development (R&D) approach to evaluate the validity of physics teaching modules based on Culturally Responsive Teaching (CRT). The development method follows the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation, including information gathering, module design, testing, and revision. The primary instrument utilized in this study is a validation sheet to assess the feasibility of the CRT-based physics teaching modules. The validity assessment was conducted by two experts using a validation sheet instrument, with the results analyzed through Aiken's V formula. The findings indicate the development of a CRT-based physics teaching module that integrates local ethnoscience relevant to physics concepts and incorporates learning strategies aligned with CRT principles. Validity assessment results demonstrate a high level of validity, confirming the module's feasibility and suitability for implementation.